'Just because she's young, it doesn't mean she has to die': exploring the contributing factors to high maternal mortality in adolescents in Eastern Freetown; a qualitative study - Lucy November; Jane Sandall (BMC, 2018)
Abstract Background In Sierra Leone, 34% of pregnancies and 40% of maternal deaths are in the adolescent population. Risks are known to be higher for younger adolescents, this being borne out by a household survey in Eastern Freetown in 2015. This current qualitative study, funded by Wellbeing of Women's international midwifery fellowship, was conducted to explore the causes of this high incidence of maternal death for younger teenagers, and to identify possible interventions to improve outcomes. Methods This qualitative study used semi-structured interviews (n = 19) and focus groups (n = 6), with a wide range of professional and lay participants, recorded with consent. Recordings were transcribed by the first author and a Krio-speaking colleague where necessary, and Nvivo software was used to assist with theming of the data around the three main research questions. Results Themes from discussions on vulnerability to teenage pregnancy focused on transactional sex, especially for girls living outside of their birth family. They included sex for school fees, sex with teachers for grades, sex for food and clothes, and sex to lessen the impact of the time-consuming duties of water collection and petty trading. In addition, the criminal justice system and the availability and accessibility of contraception and abortion were included within this major theme. Within the major theme of vulnerability to death once pregnant, abandonment, delayed care seeking, and being cared for by a non-parental adult were identified. Several obstetric risks were discussed by midwives, but were explicitly related to the socio-economic factors already mentioned. A cross-cutting theme throughout the data was of gendered social norms for sexual behaviour, for both boys and girls, being reinforced by significant adults such as parents and teachers. Conclusion Findings challenge the notion that adolescent girls have the necessary agency to make straightforward choices about their sexual behaviour and contraceptive use. For girls who do become pregnant, risks are believed to be related more to stigma and abandonment than to physical maturity, leading to lack of family-based support and delayed care-seeking for antenatal and delivery care. Two potential interventions identified within the research are a mentoring scheme for the most vulnerable pregnant girls and a locally managed blood donation register. A feasibility study of a pilot mentoring scheme is currently underway, run by the first author and a local partner.